Viral Marketing and its Impact on Brand Selection and Customer Satisfaction: A Field Study on the Employees of the University of Tabuk - بازهير، نسيم بنت عبدالغفار بن سعيد (جامعة تبوك, 2024)
تبحث هذه الدراسة في تأثير التسويق الفيروسي على اختبار العلامة التجارية. حيث هدفت الدراسة إلى فحص وتقييم استخدام التسويق الفيروسي وكيف يؤثر على تفضيل المستهلك العلامة التجارية. واستخدمت الدراسة المنهج الوصفي المسحي. وتكونت العينة من (٣٦٨) موظف من جامعة تبوك من الذكور (۱۲۰)، والإناث (٢٤٨). وقد أظهرت النتائج أن غالبية استجابات عينة الدراسة على مقياس التسويق الفيروسي كانت عالية، مما يشير إلى كبر حجم تأثير التسويق الفيروسي بين أفراد العينة. بالإضافة إلى ذلك، تجد أن هناك علاقة مباشرة بين التسويق الفيروسي وتفضيل العلامة التجارية. وستساعد هذه الدراسة مديري الشركات والمديرين التنفيذيين للتسويق وأصحاب الأعمان وجميع أصحاب المصلحة المرتبطين بها من خلال تسليط الضوء على طريقة جديدة للتفكير في استراتيجيات التسويق الفيروسي المعتمدة، والاعتراف بكيفية تأثيرها على صورة العلامة التجارية للشركة، وإدارة التعليقات السلبية حول سمعة العلامة التجارية للشركة، حيث ركزت غالبية الأبحاث حول التسويق الفيروسي على الحملات، مع قلة الاهتمام بكيفية تأثير التسويق الفيروسي على سمعة هوية الشركة. This paper examines how brand preference is affected by viral marketing. The goal of the study was to examine and assess how viral marketing is used and how it affects consumer brand preference. This study employs a descriptive relational method. The sample consisted of (368) employees of the University of Tabuk, males and females, distributed as (120) males and (248) females. The findings showed that the majority of terms on the scale for viral marketing were at a high level, indicating the perception of viral marketing among public sector personnel. Additionally, there is an almost direct correlation between viral marketing and brand preference. This paper will help company managers, marketing executives, business owners, and all associated stakeholders by highlighting a new way to think about potential viral marketing strategies, acknowledging how it will affect corporate brand image, and managing negative comments about corporate brand reputation. The majority of research on viral marketing has focused on campaigns, with little attention paid to how viral marketing affects corporate identity reputation.
Keywords: العلامات التجارية -- العمليات التسويقية -- الإعلان الفيروسي -- جامعة تبوك